The purinergic receptor P2X7 as a modulator of viral vector-mediated antigen cross-presentation - Longo, Ylenia; Mascaraque, Sara Moreno; Andreacchio, Giuseppe; Werner, Julia; Katahira, Ichiro; De Marchi, Elena; Pegoraro, Anna; Lebbink, Robert Jan; Köhrer, Karl; Petzsch, Patrick; Tao, Ronny; Di Virgilio, Francesco; et al. (Frontiers in Immunology, 2024)
Introduction Modified Vaccinia Virus Ankara (MVA) is a safe vaccine vector inducing long- lasting and potent immune responses. MVA-mediated CD8+T cell responses are optimally induced, if both, direct- and cross-presentation of viral or recombinant antigens by dendritic cells are contributing. Methods To improve the adaptive immune responses, we investigated the role of the purinergic receptor P2X7 (P2RX7) in MVA-infected feeder cells as a modulator of cross-presentation by non-infected dendritic cells. The infected feeder cells serve as source of antigen and provide signals that help to attract dendritic cells for antigen take up and to license these cells for cross-presentation. Results We demonstrate that presence of an active P2RX7 in major histocompatibility complex (MHC) class I (MHCI) mismatched feeder cells significantly enhanced MVA-mediated antigen cross-presentation. This was partly regulated by P2RX7-specific processes, such as the increased availability of extracellular particles as well as the altered cellular energy metabolism by mitochondria in the feeder cells. Furthermore, functional P2RX7 in feeder cells resulted in a delayed but also prolonged antigen expression after infection. Discussion We conclude that a combination of the above mentioned P2RX7-depending processes leads to significantly increased T cell activation via cross- presentation of MVA-derived antigens. To this day, P2RX7 has been mostly investigated in regards to neuroinflammatory diseases and cancer progression. However, we report for the first time the crucial role of P2RX7 for antigen- specific T cell immunity in a viral infection model.